Spontaneous and specific chemical cross-linking in live cells to capture and identify protein interactions. Issue 1 (December 2017) - Yang, Bing; Tang, Shibing; Ma, Cheng; Li, Shang-Tong; Shao, Guang-Can; Dang, Bobo; DeGrado, William; Dong, Meng-Qiu; Wang, Peng; Ding, Sheng; Wang, Lei
Abstract Covalently locking interacting proteins in situ is an attractive strategy for addressing the challenge of identifying weak and transient protein interactions, yet it is demanding to execute chemical reactions in live systems in a biocompatible, specific, and autonomous manner. Harnessing proximity-enabled reactivity of an unnatural amino acid incorporated in the bait toward a target residue of unknown proteins, here we genetically encode chemical cross-linkers (GECX) to cross-link interacting proteins spontaneously and selectively in live cells. Obviating an external trigger for reactivity and affording residue specificity, GECX enables the capture of low-affinity protein binding (affibody with Z protein), elusive enzyme-substrate interaction (ubiquitin-conjugating enzyme UBE2D3 with substrate PCNA), and endogenous proteins interacting with thioredoxin inE. coli cells, allowing for mass spectrometric identification of interacting proteins and crosslinking sites. This live cell chemistry-based approach should be valuable for investigating currently intangible protein interactions in vivo for better understanding of biology in physiological settings. Proteins associate via weak and transient interactions that are challenging to identify in vivo. Here, the authors use a genetically encoded chemical cross-linker to covalently lock interacting proteins in live cells, allowing them to identify the captured proteins by mass spectrometry.